Educação alimentar e nutricional : avaliação de treinamento para uso de tecnologia educativa sobre alimentos regionais - Ferreira, Ádria Marcela Vieira (2016)
The training aimed at developing knowledge, skills and attitudes of profession als currently performed activities, is indispensable for growth and professional development. The study aimed to evaluate the reaction of nurses to the trainin g workshop held and behavior of nurses trained in the use of educational techno logy on regional food. This was an evaluative research. Kirkpatrick (1998) indicates four types of evaluations for training: reaction evaluation, learning, behavior, and results. So we opted for two types of assessments: reaction evaluation and assessm ent of behavior. The study included nine nurses of the Family Health Strategy (FHS) of rural Maranguape / Ceará. Data collection occurred from August to October 2014, in four stages: training workshop with nurses, which was based on the flipchart "Regional Food promoting food security" and followed the methodology dialogue d oral presentation; Educational activity with use of flipchart by nurses in prima ry care settings to health with children of mothers in early childhood; Analysis of videos of the educational activities by the judges, which contributed to evaluation of behavior Nurses second performance levels (as expected, lower than expected or much lower than expected); and evaluation of feedback for nurses. The research p roject was approved by the Research Ethics Committee of the Federal University of Cea rá under Protocol 353/11. Regarding the nurses, all were female, mean age 3 2, formed for an average of 4.5 years, working in ESF for an average of 3.5 ye ars and the FHS of the countryside there are 2.9 years. Most had broad sense specialization (N = 7; 77.8%), but only 44.4% had participated in previous training. All the nurses performed educational activity and in groups, with the help of education al material. A training workshop on the reaction evaluation indicates that the nurses were satisfied with the training conducted, demonstrating achievement of the immediate ob jectives of the training and meeting the expectations of the participants in ad dition to the appropriate format of the course, which did not show accurately for future improvements. To analyze the reliability of the observation script used b y the judges in evaluating behavior of the nurses, identifying an overall kappa of 0.84 , representing excellent interobserver agreement and ensuring that the sam e could be applied in the evaluation of nurses to use the flipchart . Thus, after training the n urses obtained within the expected performance in more than half of the judges' ratings (> 55%) and much lower than expected in the minority of ratings (<20%). Seven nurses (87.5%) were considered suitable for the majority of the judges. Therefore, the training could be considered satisfactory, since more than 75% of nurses were considered suitable, and enabled the training of professionals to use the flipchart "Regional Food promoting food security" in the food and nutrition education for mothers of children in infancy.